Liquid biofertilizers derived from industrial effluents for cultivating protein-rich pea and chickpea - Satyanarayana; Poonam C. Singh; Rahul Mishra; Mathur Rajesh; Sunita Chauhan (Discover Applied Sciences)
Abstract Zero Hunger is one of the most important targets set under the Sustainable Development Goals (SDG). Accordingly, (SDG) 2 aims to create a world free of hunger by 2030.The global issue of hunger and food insecurity has shown an alarming increase since 2015, a trend exacerbated by a combination of factors including the COVID pandemic, armed conflicts, climate change, and deepening inequalities. The present study aims to enhance the quality and yield of chick pea and pea plants, crucial protein sources, using liquid biofertilizers derived from waste effluents of the handmade paper industry. The experiments were conducted under both in vitro and field conditions using Randomized Block Design (RBD) to evaluate the effects of raw liquor (RL) combined with various microorganisms on chickpea and pea plants. RL, a byproduct from cow dung-based handmade paper production, was used in combination with Chickpea rhizobium (CP), Bacillus species isolated from garden soil (B.st (s)), Bacillus species isolated from textile industry effluent (B.st (w)), Bacillus megaterium (BM), Phosphate solubilizing bacteria (PSB), Pea rhizobium (Pea R), and Enterobacter Kobei (ECM). In vitro, autoclaved RL and CP treatments achieved 100% germination in chickpea, with shoot and root lengths of 4.625 ± 2.0 cm and 10 ± 1.96 cm. Pea seeds treated with RL and PSB showed 100% germination, with shoot and root lengths of 2.5 ± 0.58 cm and 6.12 ± 0.63 cm for autoclaved seeds. Chickpea seeds treated with un-autoclaved RL, CP in combination with BM achieved 100% germination, with shoot and root lengths averaging 4 ± 1.46 cm and 7.125 ± 2.28 cm, and the highest number of branches. Pea seeds treated with RL, PSB, and Pea R also showed 100% germination, with the longest shoots averaging 6.6 ± 0.48 cm. Field studies showed 100% germination for chickpea with RL combined with CP treatment, and for pea with RL treatment. Chickpea root and shoot lengths were maximized with RL and CP combined with B.st (s), while pea plants showed the longest root and shoot lengths with RL combined with PSB. Yield analysis revealed the highest number of chickpea fruits with RL and CP combined with BM (33.6 ± 15.67 fruits), and the highest number of pea fruits with RL and PSB (14 ± 33 fruits). RL and PSB treatment also led to the highest fresh and dry weights and protein content in pea plants. Thus the present study establishes the recyclability and biofertilization potential of waste liquor, RL leading to sustainable agricultural practices. Future research should explore the scalability of RL-based biofertilizers across diverse crops and climatic conditions. Investigations into the long-term impacts on soil health and microbial diversity will provide a comprehensive understanding of its sustainability.